Direct Radiocarbon Dating of Rock Art. Issue 3 (18th July 2016) - Russ, Jon; Hyman, Marian; Rowe, Marvin
Abstract : In 14 C dating of pictographs, we use a low-temperature oxygen plasma coupled with high-vacuum techniques to selectively remove carbon-containing material in the paint without contamination from the rock substrate, even if limestone (CaCO3 ). In addition to one previously published measurement, we analyzed two more pictograph samples, which are in accord with archaeological inference. A sample of known age charcoal, also processed by our method, matched the control. This technique produces little mass fractionation, the maximum δ 13 C being 0.16‰ from the untreated sample. Limestone decomposition does not occur during our procedure. Although the technique development is in its infancy, these new results demonstrate that our non-destructive technique has great potential for producing accurate 14 C ages.